Culturable mycobiome of soya bean cyst nematode (Heterodera glycines) cysts from a long-term soya bean-corn rotation system is dominated by Fusarium. (December 2019) - Haarith, Deepak; Hu, Weiming; Kim, Dong-gyu; Showalter, David N.; Chen, Senyu; Bushley, Kathryn E.
Abstract: The cyst of the soya bean cyst nematode (SCN; Heterodera glycines ), an economically important pathogen of soya beans worldwide, represents a unique microhabitat in soil. The fungi inhabiting cysts may include natural antagonists of the SCN as well as saprotrophs and other opportunists. This study aimed to characterise the entire culturable mycobiome of SCN cysts obtained from a long-term soya bean-corn rotation experiment using ITS fungal barcoding. Fusarium was consistently the most frequently isolated taxon across all sampling time points and crop sequences, followed by Ilyonectria . Among fourteen genera frequently isolated from SCN cysts, five fell within the single family Nectriaceae (Sordariomycetes) and five within the order Pleosporales (Dothideomycetes), suggesting independent evolutionary origins and shared adaptations in these groups towards colonisation of SCN cysts. Six genera ( Pochonia, Clonostachys, Fusarium, Neonectria, Alternaria, and Leptosphaeria ) varied significantly by crop sequence in at least one year.